The void of mist and thunder - Dashner, James, 1972- (Dashner, James, 1972- 13th reality, 2013)
When an all-consuming void from the Fourth Dimension opens up, unleashing monsters throughout the Realities, Mister George has one last weapon at his disposal--the mysterious and powerful Karma button, which might be even more dangerous than anyone imagined.